Caracterização espectral de horizontes com e sem caráter coeso - Feitoza, Rebeca Mendes (2023)
Horizons with a cohesive character are dense subsurface pedogenetic horizons, which vary from very hard to extremely hard when dry, becoming friable or firm when wet. Soils with a cohesive character are present mainly in the Coastal Tabuleiros region, and can harm the development of crops. The genesis of the cohesive character is still debated and has been associated with temporary cementation caused by the presence of amorphous compounds. Reflectance spectroscopy is a technique that allows the spectral behavior of soils to be characterized, contributing to the generation of a spectral database. Several studies have evaluated soil attributes using reflectance spectroscopy, but there are still no specific studies with a cohesive character. Given the above, this study aimed to descriptively evaluate the variations in spectral data of horizons with and without the cohesive character of the soils collected, also evaluating the differences after removing the amorphous material. Soil samples from the states of Maranhão, Ceará, Pernambuco, Alagoas, Sergipe and Bahia were collected, with two horizons of each soil, with and without the cohesive character. Chemical and physical analyzes to determine pH, calcium, magnesium, phosphorus, sodium, potassium, aluminum, potential acidity, calculation of CEC and base saturation, organic carbon content, extraction of amorphous compounds, granulometry and fractionation of the sand were carried out for the characterization of the horizons, as well as the collection of spectral data from the samples, using the FieldSpec Pro FR spectroradiometer. The spectral curves were evaluated for their general shape across the electromagnetic spectrum, taking into account the results of chemical and physical analyses. To highlight the absorption peaks, the first derivative was applied. Data were also evaluated using cluster and principal component (PCA) analysis to identify spectrally similar samples. With reflectance spectroscopy it was possible to identify differences between the spectral curves of horizons with and without a cohesive character in the analyzed soils, mainly in terms of reflectance intensity. The use of the first derivative allowed highlighting the main features observed in the horizons of the studied soils regarding the presence of iron oxides, OH group and kaolinite. Regarding the extraction of amorphous material, reflectance was also the biggest difference observed, with a general lowering of the curves. Cluster analysis and PCA confirmed the similarities in the general shape of the curves, with reflectance intensity being the biggest factor for distinguishing the groups.